2008
DOI: 10.1111/j.1469-8137.2008.02476.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between relative growth rate and specific leaf area requires associations of specific leaf area with nitrogen absorption rate of roots

Abstract: Summary• Close correlations between specific leaf area (SLA) and relative growth rate (RGR) have been reported in many studies. However, theoretically, SLA by itself has small net positive effect on RGR because any increase in SLA inevitably causes a decrease in area-based leaf nitrogen concentration (LNC a ), another RGR component. It was hypothesized that, for a correlation between SLA and RGR, SLA needs to be associated with specific nitrogen absorption rate of roots (SAR), which counteracts the negative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 42 publications
(90 reference statements)
5
41
2
2
Order By: Relevance
“…Here we assume that these two effects cancel each other. In a data set by Osone et al (2008), the slope of the log-log relationship between photosynthetic capacity and NAR (rate of biomass increment per unit leaf mass) was close to 1 (0.91; r 2 = 0.81), which supports our idea.…”
Section: Assumptions In the Modelsupporting
confidence: 86%
See 2 more Smart Citations
“…Here we assume that these two effects cancel each other. In a data set by Osone et al (2008), the slope of the log-log relationship between photosynthetic capacity and NAR (rate of biomass increment per unit leaf mass) was close to 1 (0.91; r 2 = 0.81), which supports our idea.…”
Section: Assumptions In the Modelsupporting
confidence: 86%
“…Previous studies have shown that SAR varies greatly among species even when they are grown at the same nutrient availability and that SAR is positively related to A mass in such experiments (Garnier 1991;Poorter et al 1991;Reich et al 1998;Comas et al 2002). Figure 4 shows our experimental results from 11 herbaceous and tree seedlings grown under the same nitrogen condition (data from Osone et al 2008). A mass was correlated with neither leaf-to-plant mass ratio nor leaf-to-plant N ratio, but positively with SAR.…”
Section: Nitrogen Allocationmentioning
confidence: 57%
See 1 more Smart Citation
“…3), indicating that growth was independent of treatment for these organs not only in late autumn but also in early spring. The existence of growth correlations probably limited the thickening of old axes and root growth once shoot elongation had ceased in autumn (Sone et al 2005;Osone et al 2008). Indeed, root and axis biomass could Table 3 Trees (2012) Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A diminuição na AFE está frequentemente associada com o aumento no conteúdo de nitrogênio e fósforo por unidade de área foliar (POORTER; EVANS, 1998;REICH et al, 1999;OSONE et al, 2008), devido, em parte, ao maior acúmulo de proteínas fotossintéticas. A eficiência no uso do N foi mais elevada nas espécies com maior área foliar específica, corroborando os resultados de Poorter e Evans (1998) e Reich et al (1998).…”
Section: Mendes Kr E Marenco Raunclassified